Efficiency of Percutaneous Stent Angioplasty in Renal Artery Stenosis – 15 Years of Experience at a Single Center - Guerreiro, Helena; Avanesov, Maxim; Dinnies, Stefanie; Sehner, Susanne; Schön, Gerhard; Wenzel, Ulrich; Adam, Gerhard; Ittrich, Harald; Regier, Marc (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To determine the therapeutic efficiency of percutaneous revascularization in renal artery stenosis (RAS), as well as the role of comprehensive factors such as patient selection and degree of artery stenosis, on clinical outcome.Methods and Materials 101 patients with hemodynamically relevant RAS underwent percutaneous angioplasty (PTA). 65.7 % were male (mean age: 64 years; range: 18–84). The clinical data was retrospectively analyzed. The serum creatinine (Cr), glomerular filtration rate (GFR), and blood pressure (BP) levels pre- and postprocedural, between 6 months and 1 year, were retrospectively collected and statistically analyzed.Results Follow-up data was available in 34 (33.7 %) and 28 patients (27.7 %) for Cr and MAP, respectively. A significant drop in mean arterial pressure (MAP) was observed on follow-up (mean –5.27 mmHg). Higher baseline Cr and MAP values showed a more pronounced drop in the follow-up (Cr: p 0.002; difference to baseline –0.25 mg/dL, 95 %CI:–0.36, –0.07 and BP p < 0.001; diff. to baseline –0.72 mmHg; 95 %CI: –1.4, –0.40). There was no association between comorbidities, gender, and degree of stenosis with renal and BP outcome. No significant improvement in renal function was observed on follow-up (mean Cr drop: –0.015 mg/dL). The age group 51–60 years showed a significant improvement in BP (p 0.030; diff. to baseline –19.2 mmHg; 95 %CI: –34, –4.3). There was a slight reduction in antihypertensive medication following angioplasty (0.2 fewer). Minor complications were recorded in five procedures (4.9 %).Conclusion Percutaneous renal artery revascularization in the presence of atherosclerotic RAS is a safe procedure associated with a significant drop in post-procedural BP. No significant improvement in renal function was observed. Further prospective studies focused on patient selection are necessary.Key Points: Citation Format
Keywords: renal angiography; angioplasty; renal arteries; renovascular hypertension; atherosclerosis; renal insufficiency